Sonographic scoring of solid thyroid nodules: effects of nodule size and suspicious cervical lymph node - Unsal,Ozlem (2017)
Abstract Introduction Ultrasound is the most frequently used imaging method to evaluate thyroid nodules. Sonographic characteristics of thyroid nodules which are concerning for malignancy are important to define the need for fine needle aspiration biopsy or open surgery. Objective To evaluate malignancy risk of solid thyroid nodules through sonographic scoring. The effects of nodule size ≥2 cm and associated pathologic cervical lymph node in scoring were examined in addition to generally excepted suspicious features. Methods Medical data of 123 patients underwent thyroid surgery were reviewed, and 89 patients (58 females, 31 males) were included in the study. The presence and absence of each suspicious sonographic feature of thyroid nodules were scored as 1 and 0, respectively. Total ultrasound score was obtained by adding the positive ultrasound findings. Differently from the literature, nodule size ≥2 cm and associated pathologic cervical node were added in scoring criteria. The diagnostic performance of nodule characteristics for malignancy and the effect of total US score to discriminate malignant and benign disease were calculated. Results A significant relationship was found between malignancy and hypoechogenity, border irregularity, intranodular vascularity, and microcalcification (p < 0.05). Pathologic cervical node was observed predominantly in association with malignant nodules. Positive predictive value of suspicious cervical node for malignancy was 67%, similar to microcalcification. Nodule size ≥2 cm was not distinctive for diagnosis of malignancy. The number of suspicious sonographic features obtained with receiver operating characteristic analysis to discriminate between malignant and benign disease was three. Conclusion Sonographic scoring of thyroid nodules is an effective method for predicting malignancy. The authors suggest including associated pathologic node in the scoring criteria. Further studies with larger cohorts will provide more evidence about its importance in sonographic scoring.